2002
DOI: 10.1080/028418602753669599
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Highly Active Antiretroviral Therapy in the Treatment of HIV–Infected Patients with Systemic Non-Hodgkin‘s Lymphoma

Abstract: Twenty cases of systemic non-Hodgkin's lymphoma (NHL) in HIV-infected patients were reviewed over a 10-year-period, divided into Group A, including 13 NHL cases treated before the highly active antiretroviral therapy (HAART) era, and Group B, including 7 patients who received HAART. A Kaplan-Meier survival curve was performed and log-rank was applied to assess statistical differences between the groups. In group A, the median CD4 count was 36 cells/mm3. No complete remission was found. In group B, the median C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…Most [12–15,27,29,31], but not all [6,16–18] studies have reported improved NHL survival in the era of HAART. In a US study to 1998, there was no increase in survival in the HAART era [16], while a UK study found a nonsignificant trend ( P =0.12) towards improved survival [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most [12–15,27,29,31], but not all [6,16–18] studies have reported improved NHL survival in the era of HAART. In a US study to 1998, there was no increase in survival in the HAART era [16], while a UK study found a nonsignificant trend ( P =0.12) towards improved survival [17].…”
Section: Discussionmentioning
confidence: 99%
“…One possible factor, suggested by other studies, is receipt of HAART after NHL diagnosis. A good immunological response to HAART after NHL diagnosis was found to predict improved survival of NHL, independent of the documented response to chemotherapy, in one observational study [11], and receipt of HAART after NHL diagnosis predicted improved survival in a multivariate model of predictors of survival in a Spanish series [13], in a series from Brazil [31], in the MACS study in the US [15] and in the French Aquitaine cohort [29]. Clinical series have demonstrated that the coincident administration of HAART and chemotherapy is safe and effective [32].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the life expectation of HIV-infected individuals is approaching found in the general population. However, the available information suggests that there is an increase in the frequency of malignancies among Brazilian HIV-infected patients, as observed in other countries [ 12 , 13 ]. Unfortunately, there is scarce information on the frequency of each type of cancer and on survival time for HIV-related malignancies.…”
Section: Introductionmentioning
confidence: 96%
“…6,7 Em nosso país, entretanto, pouco é sabido sobre a incidência, o comportamento clínico e a sobrevida dos pacientes com linfoma e AIDS na era pós-HAART. 8 Em nosso serviço, a partir de 1996, passamos a utilizar quimioterapia em baixas doses associada a HAART em pacientes portadores de linfoma e AIDS. Neste estudo apresentamos o resultado de seis anos desta estratégia terapêutica.…”
Section: Introductionunclassified